Redox reactions by thermally excited charge carriers: towards sensitized thermal cells. Issue 4 (23rd May 2017) - Matsushita, S.; Tsuruoka, A.; Kobayashi, E.; Isobe, T.; Nakajima, A.
Abstract : "Sensitized thermal cells" do not rely on the Seebeck effect and do not require a temperature difference. Abstract : This study introduces a new type of system for the conversion of heat into electric power that does not require a temperature difference. This system does not rely on the Seebeck effect, and it has a simple layer-by-layer design. It is a sensitized thermal cell based on a dye-sensitized solar cell. This cell uses phonons, which are quantum expressions of heat, instead of photons. The open voltage and short-circuit current of the prototype cell, which is composed of β-FeSi2 as a semiconductor material and a solid copper ion conductor, were confirmed above 300 °C. The acquisition voltage was increased for 5 hours and continuously maintained at this value for at least 35 h, which suggests that this system functioned successfully. These generators enable all semiconductor materials to be applied three-dimensionally as heat sources, for example, in geothermal power plants, by burying the generator in a geothermal source.